2007
DOI: 10.1523/jneurosci.5474-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Inhibitory and Excitatory Transmission in the Basolateral Amygdala–Prefrontal Cortical Pathway

Abstract: Projections from the basolateral amygdala (BLA) and dopamine (DA) input from the ventral tegmental area (VTA) converge in the medial prefrontal cortex (mPFC), forming a neural circuit implicated in certain cognitive and emotional processes. However, the role that DA plays in modulating activity in the BLA-mPFC pathway is unknown. The present study investigated the mechanisms by which DA modulates BLA-evoked changes in mPFC neural activity, using extracellular single-unit recordings in urethane-anesthetized rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
149
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 77 publications
16
149
1
Order By: Relevance
“…However, once associative memories are encoded, D 4 manipulations no longer appear capable of modulating these memories, consistent with findings in single mPFC neurons (Laviolette et al, 2005). Whereas future studies are required to examine the precise neuronal basis of this effect, recent in vivo electrophysiological evidence demonstrates that D 4 receptor agonists can decrease feedforward inhibition on mPFC neurons receiving input from the BLA (Floresco and Tse, 2007), suggesting the possibility that our observed potentiation of emotional associative memory may be attributable to increasing associative information input from the BLA to the mPFC, in effect "priming" neurons in the mPFC to receive emotionally salient associative information from the BLA. We have reported previously that blockade of the D 4 receptor within the mPFC can block the encoding of emotionally salient olfactory associative learning (Laviolette et al, 2005).…”
Section: Da D 4 Receptors Modulate the Encoding Of Salient And Nonsalsupporting
confidence: 60%
See 1 more Smart Citation
“…However, once associative memories are encoded, D 4 manipulations no longer appear capable of modulating these memories, consistent with findings in single mPFC neurons (Laviolette et al, 2005). Whereas future studies are required to examine the precise neuronal basis of this effect, recent in vivo electrophysiological evidence demonstrates that D 4 receptor agonists can decrease feedforward inhibition on mPFC neurons receiving input from the BLA (Floresco and Tse, 2007), suggesting the possibility that our observed potentiation of emotional associative memory may be attributable to increasing associative information input from the BLA to the mPFC, in effect "priming" neurons in the mPFC to receive emotionally salient associative information from the BLA. We have reported previously that blockade of the D 4 receptor within the mPFC can block the encoding of emotionally salient olfactory associative learning (Laviolette et al, 2005).…”
Section: Da D 4 Receptors Modulate the Encoding Of Salient And Nonsalsupporting
confidence: 60%
“…Previous studies suggest a functional link between the BLA and mPFC both in terms of modulating DA-mediated mPFC neuronal network activity and in regulating associative encoding within mPFC neurons (Laviolette et al, 2005(Laviolette et al, , 2006aFloresco et al, 2007). We found that BLA inactivation prevented mPFC D 4 agonistmediated potentiation of memory for nonsalient fear stimuli, suggesting that mPFC D 4 modulation of emotional learning depends on functional amygdala input.…”
Section: Da D 4 Receptors Modulate the Encoding Of Salient And Nonsalsupporting
confidence: 54%
“…Previous electrophysiological recordings reported that BLA inputs exerted both inhibition and excitation of mPFC neurons. Consistent with previous reports, these findings showed that the most prominent effect of BLA stimulation seems to be an evoked inhibition of mPFC neuron firing (Floresco and Tse, 2007;Pérez-Jaranay and Vives, 1991). The glutamatergic projections from the BLA that synapse onto PV-positive GABAergic interneurons provide one potential local feedforward inhibitory effect that can suppress firing of large groups of neurons (Gabbott et al, 1997(Gabbott et al, , 2006.…”
Section: Modulatory Influence Of Bla On Vhipp-evoked Firing In Mpfc Isupporting
confidence: 92%
“…Previous in vivo electrophysiological studies suggest that ϳ60% of mPFC neurons are inhibited by electrical BLA stimulation (Floresco and Tse, 2007) and that BLAϾmPFC glutamatergic projections show a complex anatomical distribution with some terminals directly synapsing onto pyramidal neurons and others onto parvalbumin-positive GABAergic interneurons (Gabbot et al, 2006). This evidence is consistent with the present results wherein CB1 modulation within the BLA produced mixed effects on mPFC neuronal activity.…”
Section: Discussionmentioning
confidence: 99%